Peran Foto Produk Sebagai Media Promosi Untuk Meningkatkan Volume Penjualan Produk UMKM Desa Karangan - Tasya Febriyanti; Siti Ning Farida (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
This community service activity involved three MSME partners, namely the Dua Putra Putri Banana Chips UMKM, the Arjuna Coffee Powder MSME, and the Twin Princess Traditional Herbal Medicine UMKM. One of the problems faced by SMEs is the marketing process. This is based on product photos used for social media promotions that are less attractive to consumers. In product photo activities, guidance is provided on how to take good product photos. With good product photos, consumers will more easily understand an advertisement based on product photos alone. The aim of the product photo activity is to become an identity for MSME actors and can increase the value of the MSME product itself. The methods used in this community service activity are surveys and observations, interviews, discussions, and applications. The result of this community service activity is that there are enhancements to product photos that look clearer and have aesthetic value that are interesting enough to be published via e-commerce and social media such as Whatsapp, Facebook and Instragram.